Use of dietary frying palm oil in broiler chickens rations their growth performance and carcass traits - Mohammed, Mohammed Omar Abdal Qadir; Arabi, Sami Ahmed Mohammed; Mirghani, Mohamed Elwathig Saeed (ECronicon Open Access, 2021)
A study was conducted to investigate the Use of Dietary Frying Palm Oil (FPO) in Broiler Chickens Rations on body weight gain (BWG), feed intake (FI) and feed conversion ratio (FCR) in broiler chicks, haematological values, serum metabolite values and serum electrolytes and enzyme activities values. A total of 96 of the Ross 308 chicks were distributed into 4 treatments with 4 replicates/treatment (6 birds/pen) in floor brooder pens. Four treatment diets were fed from d 0 to 42: T1 (negative control without FPO), diets T2, T3 and T4 (negative control supplemented with 3, 6 and 9% Frying Palm Oil, respectively). Weekly BWG, FI and FCR were evaluated for six weeks. Feed intake per bird did not differ among the treatments during any trial periods. THE lowest BWG in chicks fed T4 and highest BWG in T3 were observed both in wk 6 (P < 0.05). FPO treatments significantly influenced FCR in all weeks overall. T3 had the highest FCR (P < 0.05), whereas the rest of the treatment diets did not differ from control diets, all levels of FPO had FCR similar to the negative control (P < 0.05). Results of the present experiment indicated that the middle level of FPO showed better BWG and the highest level of FPO showed lower BWG. haematological values red blood cell (RBC), white blood cell (WBC) and Packed Cell Volume (PCV). In 6 weeks, there was no significant difference (P < 0.05) in serum electrolytes and enzyme activities values in alanine aminotransferase (ALT), aspartate aminotransferase (AST) of chicks treated with vegetable oils compared to the control group. Total protein (TP) and urea in all treated chicks for six weeks were within the normal range were no significant increase (P < 0.05) compared to the control groups. Tenderness was affected significantly (p < 0.05) economically appraised values were profitability ratio of the test T3 was the higher of the test groups. Recycling of frying oil in poultry feed, especially frying olein oil, after ensuring that it is free from harmful substances. Adding 3 - 6% of the oil improves the carcass, the feed intake, feed conversion efficiency and the profitability margin.